DESAIN PROJECT BASED LEARNING TERINTEGRASI STEMM UNTUK MENINGKATKAN KEMAMPUAN BERWIRAUSAHA SISWA - Made Supiase; Riswandi Riswandi; Sunyono Sunyono (Akademika, 2023)
This research aims to analyze the potential and conditions, characteristics, applicability, attractiveness, student activities, and the effectiveness of using the STEMM Integrated Project Based Learning Design in the Ruminant Agribusiness Skills Competency of Ruminant Animals to improve the entrepreneurship skills of students at the Integrated Excellent State Vocational School for the 2021/2022 academic year. Data collection techniques with questionnaires and observation. The product results are in the form of STEMM Integrated Project Based Learning design development complemented by Syntax, Syllabus, RPP and LKPD. Material expert validation results for the feasibility of STEMM integrated project based learning design obtained 96% results (appropriate to use), media/design expert validation results obtained an average result of 93.5% (feasible to use), linguist validation test results obtained average results -average 92.5% (fit for use). Product testing on design implementation is 92% (can be used) and students' responses to design attractiveness are 100% (interesting). The average N-Gain Score results show that the STEM-integrated Project Based Learning Design is effective for improving students' entrepreneurship skills in the ruminant livestock agribusiness expertise competency at Integrated Excellent State Vocational School.